Genetic Aberrations of the K-ras Proto-oncogene in Bladder Cancer in Kashmiri Population - Nanda, Mahoor S.; Sameer, A. Syed; Syeed, Nidda; Shah, Zaffar A.; Murtaza, Imtiyaz; Siddiqi, Mushtaq A; Ali, Arif (Urology Journal, 2010)
PURPOSE: To assess the frequency of specific point mutations in the K-ras gene in a group of Kashmiri patients with bladder cancer. MATERIALS AND METHODS: We analyzed the incidence of K-ras exon 1 gene mutations in tumors and surgical margins in 60 patients with transitional cell carcinoma of varied clinical stages and histological grades using the polymerase chain reaction-single strand conformation polymorphism and DNA sequencing. RESULTS: A significant correlation was found between the K-ras, the lymph node status, and tumor recurrence (P < 0.05). Also, smokers and patients with higher tumor grade showed a significantly higher relative risk of developing K-ras mutations than the normal ones. CONCLUSION: K-ras exon 1 gene mutations were found with low frequency in the bladder cancer tumors from Kashmir valley, which suggests that K-ras gene might be involved in a sub-set of bladder tumors, but it needs further investigation on a larger cohort sample to authenticate the current findings.